Privatized healthcare for older adults living with chronic illness: A scoping review protocol for synthesizing the state of knowledge on their experiences - Stuart McKinlay; Christine L. Sheppard; Paige Brown; Luxey Sirisegaram; Kristina M. Kokorelias (PLoS ONE, 2025)
As global populations age, the prevalence of chronic illness among older adults is increasing, intensifying the burden on healthcare systems. Research shows that today’s older adults, especially those over 65, are more likely to suffer from multiple chronic conditions than previous generations. This demographic shift underscores the urgent need for healthcare systems capable of addressing complex, long-term health needs. The rise of privatized healthcare—services provided by non-governmental entities and funded through private insurance or out-of-pocket payments—has become a significant feature of the healthcare landscape, affecting how older adults receive care. In contrast to public healthcare systems, which are government-funded and aim to ensure universal coverage, privatized models often involve substantial private costs. Hybrid systems, such as those in Australia, combine public and private elements to offer comprehensive services. However, even in predominantly public systems like Canada, private costs for non-covered services persist. This scoping review protocol outlines a plan to identify (1) the potential role of privatized healthcare models in countries with public or hybrid healthcare in addressing health needs, (2) challenges and limitations associated with these models for older adults living with chronic conditions, and (3) current gaps in knowledge regarding the impact of privatized healthcare on care outcomes for older adults, based on the available literature.. It aims to explore the experiences and challenges of this population across various countries with public or hybrid healthcare systems. The review will use a structured methodology based on the Arskey and O’Malley guidelines and the Joanna Briggs Institute framework, focusing on qualitative studies published in the past 20 years. By comparing findings across different settings, the review seeks to provide a comprehensive understanding of how privatized healthcare models affect older adults and inform future research and policy development.